Pengaruh Pembiayaan Murabahah dan Musyarakah terhadap Profitabilitas (Studi pada Bank BTPN Syariah Periode Juni 2019-September 2020) - Yonaya Salma; Wirman Wirman (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
This study aims to examine: (1) The Effect of Murabahah Financing on Profitability (ROE) (2) The Effect of Musyarakah Financing on Profitability (ROE). This study uses secondary data, the population in this study is the BTPN Syariah Bank. The data used is drived from the quarterly financial statements of BTPN Syariah Bank for the period June 2019 – September 2020. The sampling technique in this study is multiple linear, regression, and test the classical assumption of nor- mality test, multikoloniaritas, heteroksidasitas, and autokorolation, while proving the hypothesis of determination R2, F statistical test, and the test T statistic. The result show that murabahah financing variable (X1) is negative value and has no effect on ROE (Y). While musyarakah financing variable (X2) is positive value and has no effect on ROE (Y).